Structural and functional composition of fish communities associated to Zostera noltii meadows as a response to natural habitat recovery - Nuno Castro (2019)
During 2008, the Zostera noltii meadows located in the lower Mira estuary (SW Portugal) disappeared completely. However, during 2009, symptoms of natural recovery were observed, and in 2015 totally mature patches were detected. This allowed to investigate the temporal and spatial distribution patterns of the composition and structure of ichthyofaunal communities under two distinct habitat ecological conditions: before the collapse of mature vegetation of seagrass beds, in the 1980s (historical data), and after the natural habitat recovery process (new data). Significant differences were detected in the fish communities i) before and after the recovery process; and ii) in the seagrass beds and adjacent bare areas before the collapse, but no differences were observed after the natural recovery between seagrass fish communities and bare adjacent areas. Fish communities of seagrass beds in the 1980s were, in general, characterized by higher values of species richness, diversity and abundance. Apparently, the collapse of seagrass beds led to the disappearing of some fish species and to a decrease in abundance of others. Generally, such fish species have not returned to the system or recovered the population status during this early recovery process. This study addressed significant shifts that occurred in the lower Mira estuary fish communities in the last 30 years. Climate change may have influenced those alterations, although the event of the seagrass beds collapse seems to be the main driver of the community shifts.